Organizational Strategy, Structure, and Process - Miles, Raymond E.; Snow, Charles C.; Meyer, Alan D.; Coleman, Henry J. (Academy of Management Review, 1978)
Organizational adaptation is a topic that has received only limited and fragmented theoretical treatment. Any attempt to examine organizational adaptation is difficult, since the process is highly complex and changeable. The proposed theoretical framework deals with alternative ways in which organizations define their product-market domains (strategy) and construct mechanisms (structures and processes) to pursue these strategies. The framework is based on interpretation of existing literature and continuing studies in four industries (college textbook publishing, electronics, food processing, and health care).